Conversational Implicature in Short Story "My Enemy but My Love" by Limya’ Shaheen - Hafizh Ananda, Rayhan (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2023)
Implicature can occur anytime and anywhere as long as there are speakers and interviewers present at the same time. This research aims to describe the types and functions of conversational connotations in the short story “My Enemy but My Love” by Limya’ Shaheen based on Grice’s perspective. This type of research is descriptive qualitative research. The primary data source is the short story “My Enemy but My Love” by Limya’ Shaheen and the secondary data are books and magazines related to the research. Data collection techniques were implemented using reading techniques, translation techniques, and note-taking techniques. Data validation techniques are performed by collecting relevant theories, making conclusions, and reviewing research findings. The research analysis techniques used are data reduction, data presentation and making conclusions. This research reached the following results: (1) there are 2 functions of particularized conversational implicatures in the form of innuendo and hope. (2) there are 3 functions of generalized conversational implicatures in the form of praise, curiosity and statement. (3) there is 2 function of the type of scalar implicature in the form of a statement and innuendo. يمكن أن يحدث التضمين في أي وقت وفي أي مكان طالما أن هناك متحدثين ومحاورين حاضرين في نفس الوقت. يهدف هذا البحث إلى وصف أنواع ووظائف الدلالات التخاطبية في القصة القصيرة "عدوي لكن حبيبي" للمياء شاهين من وجهة نظر جريس. هذا النوع من البحث هو بحث نوعي وصفي. مصدر البيانات الأساسي هو القصة القصيرة "عدوي لكن حبيبي" للمياء شاهين والبيانات الثانوية هي الكتب والمجلات المتعلقة بالبحث. تم تنفيذ تقنيات جمع البيانات باستخدام تقنيات القراءة وتقنيات الترجمة وتقنيات تدوين الملاحظات. يتم تنفيذ تقنيات التحقق من صحة البيانات من خلال جمع النظريات ذات الصلة، واستخلاص النتائج، ومراجعة نتائج البحث. تقنيات تحليل البحث المستخدمة هي تقليل البيانات وعرض البيانات واستخلاص النتائج. وقد توصل هذا البحث إلى النتائج التالية: (1) هناك وظيفتان دلاليتان محددتان للتخاطب في شكل التلميحات والتوقعات. (2) هناك ثلاث وظائف للدلالة التخاطبية العامة وهي المدح، والفضول، والبيان. (3) هناك وظيفتان لأنواع التضمين العددي في شكل بيانات وتعليمات.